Environmental conditions to support blue carbon storage in mangrove forest: A case study in the mangrove forest, Nusa Lembongan, Bali, Indonesia - Cindy Clara Pricillia; Herdis Herdiansyah; Mufti Petala Patria (Biodiversitas Journal of Biological Diversity, 2021)
Abstract. Pricillia CC, Patria MP, Herdiansyah H. 2021. Environmental conditions to support blue carbon storage in mangrove forest: A case study in the mangrove forest, Nusa Lembongan, Bali, Indonesia. Biodiversitas 22: 3304-3314. Mangrove ecosystems can provide ecosystem services to mitigate climate change by absorbing and storing carbon in their systems. The question arises of how to manage a mangrove forest to store more carbon. The Nusa Lembongan mangrove forest was examined to assess the optimal environmental settings for blue carbon storage in the mangrove ecosystem. Five stations were selected purposively. The parameters observed in each station were aboveground living biomass, mangrove stand density, clay percentage in soil, bulk density, water content, soil organic carbon (%C), and soil organic nitrogen (%N). Based on this study, the total carbon stock in mangrove forest Nusa Lembongan was 68.10 ± 20.92 Mg C ha-1 and equals to 249.95 ± 76.77 MgCO2 ha-1 with a significant contribution of soil carbon stock. This study indicates that the essential parameters that can promote carbon sequestration in mangrove forest Nusa Lembongan were aboveground living biomass, soil organic carbon content and soil organic nitrogen content. In addition, as soil organic carbon content also negatively correlates with bulk density, it also can be considered. These findings can contribute to blue carbon planning and management to improve the effectiveness of the blue carbon project.